PERANCANGAN SISTEM INFORMASI MORBIDITAS RAWAT INAP DI RUMAH SAKIT X - Indra Setia Budi; Yuda Syahidin; Irda Sari (LPSDI Bina Patria, 2023)
The reporting system in medical record computerized was implemented in the Hospital X being limited in terms of the process of reporting morbidity kodefikasi disease is still being processed using Microsoft Excel resulting in a lack of efficiency reporting the need either, monthly period, semester period and year period. This study attempts to get hospital information system design information systems kodefikasi in-patient disease in using microsoft Visual Studio 2010 and Microsoft Acces 2010. Researchers in a waterfall and easier to control one by one the design and minimize the blame to be possible. Medical record information system is expected to help the Hospital X, in order to increase the quality of service , professional and the costs. resource efficiency.